1996
DOI: 10.1091/mbc.7.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a single monolayer tubulin-GTP cap is both necessary and sufficient to stabilize microtubules.

Abstract: Evidence that 13 or 14 contiguous tubulin-GTP subunits are sufficient to cap and stabilize a microtubule end and that loss of only one of these subunits results in the transition to rapid disassembly (catastrophe) was obtained using the slowly hydrolyzable GTP analogue guanylyl-(a,b)-methylene-diphosphonate (GMPCPP). The minus end of microtubules assembled with GTP was transiently stabilized against dilution-induced disassembly by reaction with tubulin-GMPCPP subunits for a time sufficient to cap the end with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
2
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 27 publications
7
120
2
3
Order By: Relevance
“…Prediction of strong longitudinal bonds and relatively weak lateral bonds is in agreement with structural observations (18). We also estimated that the potential mechanical energy of tubulin-GDP conformational stress in the MT lattice is 2.1-2.5 k B T, in approximate agreement with thermodynamic studies that suggest Ϸ2.8 k B T per tubulin-GDP is stored in the MT lattice (14,22,23).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Prediction of strong longitudinal bonds and relatively weak lateral bonds is in agreement with structural observations (18). We also estimated that the potential mechanical energy of tubulin-GDP conformational stress in the MT lattice is 2.1-2.5 k B T, in approximate agreement with thermodynamic studies that suggest Ϸ2.8 k B T per tubulin-GDP is stored in the MT lattice (14,22,23).…”
Section: Discussionsupporting
confidence: 86%
“…Catastrophe frequency simulations began with an MT capped by 4 GTP-tubulin layers (52 dimers) and ran until the GTP-cap size (number of tubulin-GTP dimers) was zero. Experiments by Caplow and Shanks (14) suggested that Ͻ13 tubulin-GTP dimers at a MT tip would result in catastrophe. Here we used complete loss of the GTP cap as a convenient way to mark a catastrophe.…”
Section: Methodsmentioning
confidence: 99%
“…For in vivo situation, the effective kinetochore diffusion coefficient includes the large chromosome effect and thus it is very small Ϸ400-800 nm 2 ͞s. Because the microtubule bending strain is usually low (Ϸ3 k B T) [this value is supported by experimental measurement (23) and theoretical calculations (21,22)], it alone could not drive the kinetochore to overcome local binding potential Ϸ12.5 k B T (5,14,19). Thus, according to Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Upon microtubule depolymerization, the bending strain is released and provides a driving force for the kinetochore translocation (2,12,20). However, given the strong attachment of the kinetochore to microtubule of Ϸ12.5 k B T (5,14,19), as our calculations in this paper suggest, a bending strain of Ϸ3 k B T (2,3,(20)(21)(22)(23) is not sufficient. It has also been proposed that a ratchet-like biased one-dimensional diffusion model could account for the kinetochore translocation (17).…”
mentioning
confidence: 77%
See 1 more Smart Citation